Predictive Modelling and AI Integration for Enhanced Analysis of Warranty and Notification Data ; A Case Study in Manufacturing Data Analysis - Ojala, Siiri (My University, 2024)
This thesis explores the application of predictive modelling and AI integration in the analysis of warranty and notification data within a manufacturing company context. The research aims to develop a Power BI tool to analyze and visualize the relationship between warranty and notification data while utilizing predictive analytics. Design science methodology, specifically the Design Science Research Methodology (DSRM), is employed in the research process. The research objectives are threefold: (1) to investigate how predictive models can be utilized to analyze warranty and notification data, (2) to identify factors in the warranty and notification data connected to warranty claims, and (3) to explore potential future applications of AI in analyzing warranty and notification data in the next 10 years. Methodologically, logistic regression and time series analysis are employed to develop predictive models. Logistic regression is utilized to predict product claims, while time series analysis is used to visualize trends and offer forecasting options within Power BI. Additionally, AI-powered tools such as the key influencers in Power BI are utilized to analyze factors affecting product claims. Key findings indicate a significant positive relationship between notification count and the probability of a product claim, validating the original hypothesis. Recommendations for the case company include investing in augmented analytics, democratizing AI within the organization, and prioritizing clear communication to ensure effective and ethical use of AI technologies. While the research demonstrates the effectiveness of predictive modelling and AI integration in warranty and notification data analysis, several limitations exist. These include the inability to fully integrate the logistic regression model into Power BI and the focus primarily on the probability of product claims, leaving other potential areas unexplored. In conclusion, this thesis marks a step towards transforming warranty data into a tool for risk management and product improvement. Future research directions include refining predictive models, exploring advanced AI techniques, and increasing the generalizability of findings across different industries.

Tässä tutkielmassa syvennytään ennustemallintamisen ja tekoälyn integroinnin vaikutuksiin takuu- ja notifikaatiodatan analysoinnissa valmistavassa yrityksessä. Tutkielman päätavoitteena on kehittää ennustemallintamiseen perustuva Power BI -työkalu, jonka avulla voidaan analysoida ja visualisoida takuu- ja notifikaatiodatan välistä suhdetta. Tutkimuksessa käytetään suunnittelutieteellistä metodologiaa, joka mahdollistaa järjestelmällisen lähestymistavan ongelmanratkaisuun ja uusien ratkaisujen kehittämiseen. Tutkielman tavoitteita on kolme: (1) tutkia ennustemallien soveltamista takuu- ja notifikaatiodatan analysoinnissa, (2) tunnistaa takuu- ja notifikaatiodatasta tekijöitä, jotka vaikuttavat reklamaatioihin, sekä (3) tutkia mahdollisia tapoja hyödyntää tekoälyä takuu- ja notifikaatiodatan analyysiin seuraavan vuosikymmenen aikana. Tutkielmassa ennustemallien luonnissa hyödynnetään logistista regressiota ja aikasarja-analyysiä. Logistista regressiota käytetään ennustamaan reklamaatioita, ja aikasarja-analyysiä hyödynnetään tulevan kehityksen ennustamiseen ja visualisointiin. Lisäksi työssä käytetään tekoälypohjaisia työkaluja, kuten Power BI:n tärkeimmät vaikuttajat -työkalua. Tutkielmassa löydettiin merkittävä positiivinen suhde notifikaatiomäärän ja reklamaatiotodennäköisyyden välillä. Näiden tulosten perusteella case-yritystä suositellaan panostamaan entistä enemmän tekoälypohjaiseen analytiikkaan sekä lisäämään ja laajentamaan tekoälyosaamista organisaatiossa. Lisäksi selkeä ja avoin kommunikaatio on keskeisen tärkeää, jotta tekoälyn tehokas ja eettinen käyttö voidaan varmistaa. Vaikka tutkimuksen tulokset osoittavat ennustemallintamisen ja tekoälypohjaisten työkalujen tehokkuuden takuu- ja notifikaatiodatan analysoinnissa, tutkimuksen rajoituksiin kuuluu logistisen regressiomallin epätäydellinen integrointi kehitettyyn työkaluun sekä keskittyminen pääasiassa tuotereklamaatioihin. Tulevaisuudessa tutkimusta voidaan laajentaa tarkastelemalla muita ennustemalleja ja tekoälytyökaluja sekä tutkimalla aihetta eri toimialoilla ja konteksteissa.
Keywords: mallintaminen; analyysi; data; business intelligence; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management